KEPEMIMPINAN DAN PENGEMBANGAN KARIR TERHADAP KOMITMEN ORGANISASIONAL SERTA DAMPAKNYA PADA KINERJA KARYAWAN PT. BANK MANDIRI (PERSERO) TBK AREA MAKASSAR KARTINI - Nabila Mutiasari Yunus; Nurdjanah Hamid; Ria Mardiana Yusuf (Hasanuddin Journal of Applied Business and Entrepreneurship, 2018)
A good organization, growing and developing will focus on human resources to perform its functions optimally. This study aims to (i) know the influence of leadership variables on organizational commitment; (ii) to know the effect of career development variable on organizational commitment; (iii) to know the effect of organizational commitment variable on employee performance; (iv) to know the influence of leadership variables indirectly on employee performance through organizational commitment; and (v) determine the effect of career development variables indirectly on employee performance through organizational commitment. This research design uses survey method. This research was conducted at PT. Bank Mandiri (Persero) Tbk area of Makassar Kartini. Methods of data collection conducted in this study are questionnaires, documentation techniques and literature techniques. The population of this study are permanent employees of PT. Bank Mandiri (Persero) Tbk Area Makassar Kartini for 452 employees. Determination of the number of samples is done by using the formula of Slovin, so that the number of samples obtained as many as 82 people. Analytical techniques used are validity test, reliability test, descriptive analysis, and path analysis. The results showed that the variable of leadership variable significantly influence organizational commitment. Career development has a significant effect on organizational commitment. Organizational commitment has a significant effect on employee performance. Leadership variables indirectly affect the performance of employees through organizational commitment, and career development have an indirectly significant impact on employee performance through organizational commitment. Keywords: leadership, career development, organizational commitment, employee performance, and bank